ANALISIS KESULITAN SISWA DALAM BERBICARA BAHASA INGGRIS DI MAS MULIA SEI BALAI - Sulaiman Ahmad (CV. ADIBA AISHA AMIRA, 2024)
English speaking skills are the main skills that show language proficiency. However, most students experience barriers or difficulties in speaking. Therefore, the purpose of this research is to identify the difficulties or obstacles experienced by students in learning English, especially in improving speaking skills. The research subjects were students of the Private Islamic Senior High School (MAS) Mulia Sei Balai. The research method uses descriptive qualitative. Research data obtained through interviews and observation. The data obtained were analyzed using four stages, namely data collection, data presentation, data reduction, and verification/conclusion. Based on the results of data analysis, it can be concluded that the difficulties experienced by students in speaking English are caused by five factors, namely lack of vocabulary, pronunciation/pronunciation, not having friends or partners in speaking, lack of confidence, and the atmosphere of the language learning class English tends to be monotonous and boring.